أثر الاداء اللوجستي على نمو الصادرات خارج قطاع المحروقات دراسة مقارنة بين الجزائر والسعودية - قدة جميلة (university Of Eloued جامعة الوادي, 2024)
استهدفت هذه الدراسةأثر الأداء اللوجستي على نمو الصادرات خارج قطاع المحروقات لحالة الاقتصاد الجزائري مقارنة مع حالة اقتصاد المملكة العربية السعودية خلال الفترة من الربع الأول لسنة2007 إلى الربع الرابع لسنة 2023، حيث تم استخدام متغيرين اثنين يمثلان الأداء اللوجستي وهما: مؤشر الربط بالشحن البحري المنتظم ومؤشر عبء الإجراءات الجمركية. وتوصلت الدراسة من خلال استخدام نموذج الانحدار الذاتي للفجوات الزمنية ARDL إلى أن مؤشر الربط بالشحن البحري المنتظم ومؤشر عبء الإجراءات الجمركية في الجزائر لهما أثر إيجابي ومعنوي إحصائيا في الأجل الطويل على الصادرات خارج قطاع المحروقات عند مستوى معنوية 5 %،أما في المملكة العربية السعودية فمؤشر الربط بالشحن البحري المنتظم له أثر إيجابي ومعنوي عند مستوى 5 %، غير أن أثر مؤشر عبء الإجراءات الجمركية لم يكن معنويا عند 5%، أما في الأجل القصير فبناءعلىنموذجاختبارتصحيحالخطأ تبين بأنه إذاحدثتصدمةفيمؤشراتالأداءاللوجستي فإن أثرها علىالصادراتخارجقطاعالمحروقات تدوم في الجزائر مدة 14 شهرا وفي السعودية مدة 11 شهرا ليعود إلى وضعه التوازني. Abstract: This study aimed to examine the impact of logistics performance on the growth of non-hydrocarbon exports in the Algerian economy compared to the Saudi Arabian economy during the period from the first quarter of 2007 to the fourth quarter of 2023. Two indicators representing logistics performance were employed; the regular maritime shipping connectivity index and the customs procedures burden index. The study, using the Autoregressive Distributed Lag (ARDL) model, found that the regular maritime shipping connectivity index and the customs procedures burden index in Algeria have a positive and statistically significant long-term impact on non-hydrocarbon exports at a 5% significance level. In Saudi Arabia, the regular maritime shipping connectivity index also has a positive and significant impact at the 5% level, but the impact of the customs procedures burden index was not significant at 5%. In the short term, based on the error correction model, the study reveals that if there is a shock in logistics performance indicators, its impact on non-hydrocarbon exports lasts for 14 months in Algeria and 11 months in Saudi Arabia before returning to equilibrium.
The impact of logistic performance on the growth of exports outside the hydrocarbons sector a comparative study between Algeria and Saudi Arabia
أطروحة دكتوراه تخصص التجارة الدولية والخدمات اللوجستيةكلية كلية العلوم الإقتصادية والتجارية وعلوم التسيير جامعة الوادي
Keywords: أداء لوجستي; ربط بالشحن البحري المنتظم; عبء الإجراءات الجمركية; صادرات خارج قطاع المحروقات; نموذج الانحدار الذاتي للفجوات الزمنية ARDL; Logistics performance; maritime shipping connectivityregular; customs procedures burden; non-hydrocarbon exports; Autoregressive Distributed Lag (ARDL) model.